2007
DOI: 10.1111/j.2007.0030-1299.15781.x
|View full text |Cite
|
Sign up to set email alerts
|

Post-invasion evolution of native plant populations: a test of biological resilience

Abstract: Contemporary evolution may explain the success of some exotic plant invasions. However, the evolutionary response of recipient native plant populations to exotic invasion has received relatively little attention. Because plant populations are genetically variable, contemporary evolution may also occur in native populations following entry of invasive species. Previously, we documented molecular differences in native populations; here we extend these studies to evaluate growth of native species in a common gard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 32 publications
2
28
1
Order By: Relevance
“…Their results indicated that a small portion of loci may be linked to genes undergoing selection caused by Acroptilon invasion. In a second experiment, S. airoides genets collected from old Acroptilon patches showed consistently greater growth when transplanted into other patches of Acroptilon than genets collected patches with no Acroptilon, suggesting that some native species have the potential for adaptation to coexist with this invader (Mealor and Hild 2007; also see Callaway et al 2005).…”
Section: Discussionmentioning
confidence: 91%
“…Their results indicated that a small portion of loci may be linked to genes undergoing selection caused by Acroptilon invasion. In a second experiment, S. airoides genets collected from old Acroptilon patches showed consistently greater growth when transplanted into other patches of Acroptilon than genets collected patches with no Acroptilon, suggesting that some native species have the potential for adaptation to coexist with this invader (Mealor and Hild 2007; also see Callaway et al 2005).…”
Section: Discussionmentioning
confidence: 91%
“…Remnant native grasses remaining following invasions are not normally included in native seed collections. But, for reasons argued above and elsewhere (Mealor et al 2004; Mealor & Hild 2006, 2007), we suggest that remnant subpopulations may provide alternative seed sources to establish desirable native species communities with increased resistance against exotic invaders (Leger 2008).…”
Section: Introductionmentioning
confidence: 58%
“…The length of knapweed presence for each site was estimated to be from 40 to 75 years based on published literature and herbarium records (Mealor & Hild 2006). Invaded and non‐invaded communities were delineated by a clear absence of A. repens in the non‐invaded type, and were separated by less than 20 m at each location (Mealor & Hild 2007). We randomly collected 10 maternal plants from each community type at each location by hand‐excavating approximately 25‐cm diameter plant portions, which were transported to greenhouse facilities at the University of Wyoming, Laramie, Wyoming, U.S.A.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations